Facilitating College Supports to Ensure Student Success. Issue 160 (5th December 2018) - Fowler, Catherine H.; Getzel, Elizabeth Evans; Lombardi, Allison
Abstract: This chapter examines the changes in supports and services from secondary to postsecondary for students with disabilities. It recommends ways organizations, practitioners, and students must coordinate and collaborate to affect the environment and increase student success in postsecondary education.